Patient Safety Culture among Nurses: Case Study - Dangan Panggalih; Silfia Sekar Arum Mandalia Elly Susanti (Babali Publisher, 2023)
Introduction: Patient safety is the concerted effort to prevent errors in healthcare procedures that may endanger patients. Every healthcare provider faces the risk of making mistakes in delivering healthcare services, potentially jeopardizing patient safety. This study aims to assess the patient safety culture among nurses at Gambiran Hospital, identify strengths, weaknesses, opportunities, and threats (SWOT), and formulate strategies for Gambiran Hospital. Methods: This quantitative study employed a case study design conducted at Gambiran Hospital. A total of 150 respondents were selected using a total sampling technique, and data were collected through the distribution of questionnaires. Data analysis was conducted using univariate analysis. Results: The prioritization of issues is essential to develop strategies aimed at improving the patient safety culture among nurses. This approach ensures that nurses are more receptive to reporting incidents (RRI) during their shifts. Conclusion: Assessing the patient safety culture among nurses in the Dhaha room is crucial, as it encourages nurses to report incidents and facilitates the socialization of initiatives aimed at enhancing patient safety culture among nurses.